Guava Juice Reduces Cholesterol Level for Elderly with Hypertension - Dian Rahma Afitasari; Ah. Yusuf; Fery Effendi (Universitas Airlangga, 2010)
Introduction: Hypertensive disease is closely related to high cholesterol level, which may act as one of causes of death in elderly. The objective of this study was to analyze the effect of guava juice on the reduction of cholesterol level of hypertensive elderly at Community Health Center, Pacar Keling, Surabaya.Methods: Quasy–experimental was used in this study. Sample comprised of 14 respondents who met the inclusion criteria. The independent variable was guava juice and the dependent variable was cholesterol level. Data were collected using questionnaire and observation. Data were analyzed by Paired t–Test and Independent t–Test with signi fi cance level of α < 0.05.Results: The result showed that guava juice gave a significant effect to cholesterol level of elderly with hypertension (p = 0.000).Conclusion: It can be concluded that guava juice can reduce cholesterol level in elderly with hypertension. The reduction of cholesterol level may result from vitamin C, pectin, and potassium contained in guava juice, which have effect on cholesterol regulation in the body. Guava juice can be provided as daily diet for elderly. Further studies are suggested to investigate other variables, such as diet consumed, age, activity, and obesity.